Association between Body Condition Score and Cancer Prognosis in Dogs with Lymphoma and Osteosarcoma. (8th June 2016) - Romano, F.R.; Heinze, C.R.; Barber, L.G.; Mason, J.B.; Freeman, L.M.
Abstract : Background: In humans and rodents obesity appears to promote some cancers by increasing incidence, tumor aggressiveness, recurrence, and fatality. However, the relationship between obesity and cancer in dogs has not been thoroughly evaluated. Hypothesis/Objectives: Whether body condition score (BCS) at the time of lymphoma (LSA) or osteosarcoma (OSA) diagnosis in dogs is predictive of survival time (ST) or progression‐free interval (PFI). We hypothesized that an overweight body state at the time of cancer diagnosis would be associated with negative outcomes. Animals: Dogs with LSA (n = 270) and OSA (n = 54) diagnosed and treated between 2000 and 2010. Methods: Retrospective case review. Signalment, body weight, BCS, cancer diagnosis and treatment, relevant clinicopathologic values, and survival data were collected. Dogs were grouped by BCS (underweight, ideal, and overweight) and ST and PFI were compared. Results: Overall, 5.5% of dogs were underweight, 54.0% were ideal weight, and 40.4% were overweight at diagnosis. Underweight dogs with LSA had shorter ST ( P = .017) than ideal or overweight dogs. BCS was not associated with ST for OSA ( P = .474). Progression‐free interval did not differ among BCS categories for either cancer. Conclusions and Clinical Importance: Obesity was not associated with adverse outcomes among dogs with LSA or OSA in this retrospective study; however, being underweight at the time of diagnosis of LSA was associated with shorter survival. More research is needed to elucidate the relationship between excessive body weight and cancer development and progression in dogs.